Community Conditions After The Flash Flood Disaster in The Nagari Batahan Barat River Basin, Pasaman Barat Regency - Uzzahara, Vivi Fatimah; Juita, Erna; Zuriyani, Elvi (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2023)
Flash floods are inundations caused by runoff out of river channels because river discharge suddenly increases beyond the capacity of river flows. It occurs quickly and hits residential areas with low relief, in river valleys and basins, and usually brings discharge in the flow. As a result of high rainfall for 3 to 4 days, has caused many physical and social losses, including 255 houses being flooded. This research is classified as a mixed methods research type. The sampling technique was taken using a proportional random sampling technique to collect information for this research using a snowball sampling technique. For analysis of questionnaire data, it is measured using a Likert scale. The results of this research include that the residential conditions of the people of Nagari Batahan Barat were clean before the flash flood occurred, after the flash floods were not clean, the condition of the livelihood of Nagari Batahan Barat people, in general, was gardening and/or farming, the condition of the plantations and agriculture of Nagari Batahan Barat people, Pasaman Barat Regency before the flash flood occurred, and the condition of the community's plantations and agriculture after the flash flood was not good.